ПОДАННЯ ІНФОРМАЦІЇ В КОМП’ЮТЕРНО ОРІЄНТОВАНИХ ОСВІТНІХ ТЕХНОЛОГІЯХ ТА ЇЇ ЕКСПЛІКАЦІЯ В ІМПЕРАТИВАХ ПОСТМОДЕРНІЗМУ - Stezhko, Yurii G. (Information technologies and learning tools, 2019)
The article highlights the performance and features of the application of information and educational technologies, the embodiment of which presents education at the level of a strategic resource for social and economic development. The role of computerization of educational technologies in the era of modernity and postmodern is being compared; the boundaries of effective application of formalization of reality in algorithms are outlined. The thought of the conditionality of information content by specifics of computer representation, the requirements of logical verification is carried out. It is said that the absolute domination in the era of modernism in the educational information technology of formal-logical rationality has had a detrimental effect on the humanistic component of social intelligence. Postmodernist imperatives encourage methodologists of information provision of education to recognize a wide range of types of rationality, in the content of which great importance is the weakening of logical correction in favor of strengthening the irrational component, subjectivity as creativity. It is postulated that it is inappropriate to determine the evaluation models of information on which the educational process is based, based only on the classical rationality in marking the truth and its criteria. The educational process in the competence model is oriented towards pragmatism and is therefore characterized by methodological pluralism, where any methodology can become the leading one depending on the didactic purpose, and the forms and methods of cognition are chosen situationally, based on the parity of the rational and irrational components of knowledge. Postmodern intellectualism has grown on the diversity of forms of comprehension of reality, on the syncretism of computer and human intelligence in educational technologies. It is noted that every civilizational transformation causes a reassessment of the semantic priorities of information, the relativization of forms of cognition, rethinking the criteria for assessing the level of socio-intelligence. At present, the prospect of innovative development of education is seen in the modernization of methodological culture and the very way of thinking of educators. Education should evolve ahead of civilization challenges.